DdPCR surpasses classical qPCR technology in quantitating bacteria and fungi in the environment. (2nd June 2022) - Wang, Danrui; Wang, Shang; Du, Xiongfeng; He, Qing; Liu, Yue; Wang, Zhujun; Feng, Kai; Li, Yan; Deng, Ye
Abstract: Quantitative real‐time PCR (qPCR) has been widely used in quantifying bacterial and fungal populations in various ecosystems, as well as the fungi to bacteria ratio (F:B ratio). Recently, researchers have begun to apply droplet digital PCR (ddPCR) to this area; however, no study has systematically compared qPCR and ddPCR for quantitating both bacteria and fungi in environmental samples at the same time. Here, we designed probe‐primer pair combinations targeting the 16S rRNA gene and internal transcribed spacer (ITS) for the detection of bacteria and fungi, respectively, and tested both SYBR Green and TaqMan approaches in qPCR and ddPCR methods for mock communities and in real environmental samples. In mock communities, the quantification results of ddPCR were significantly closer to expected values ( p  < .05), and had smaller coefficients of variations ( p  < .05) than qPCR, suggesting ddPCR was more accurate and repeatable. In environmental samples, ddPCR consistently quantified ITS and 16S rRNA gene concentrations in all four habitats without abnormal overestimation or underestimation, and the F:B ratio obtained by ddPCR was consistent with phospholipid fatty acid analysis. Our results indicated that ddPCR had better precision, repeatability, sensitivity, and stability in bacterial and fungal quantitation than qPCR. Although ddPCR has high cost, complicated processes and restricted detection range, it shows insensitivity to PCR inhibitors and the potential of quantifying long target fragments. We expect that ddPCR, which is complementary to qPCR, will contribute to microbial quantification in environmental monitoring and evaluation.